Sleep Variability in Military-Related PTSD: A Comparison to Primary Insomnia and Healthy Controls - Straus, Laura D.; Drummond, Sean P. A.; Nappi, Carla M.; Jenkins, Melissa M.; Norman, Sonya B. (Journal of traumatic stress, 2015)
Sleep disturbances are prevalent in posttraumatic stress disorder (PTSD) and are associated with a number of adverse health consequences. Few studies have used comprehensive assessment methods to characterize sleep in Operation Iraqi Freedom/Operation Enduring Freedom/Operation New Dawn (OEF/OIF/OND) veterans with PTSD. OEF/OIF/OND veterans with PTSD and sleep disturbance (n = 45) were compared to patients with primary insomnia (n = 25) and healthy control subjects (n = 27). Participants were assessed using questionnaire‐based measures as well as daily subjective and objective measures of sleep. The 3 groups were compared with regard to (a) group means, (b) intraindividual (i.e., night‐to‐night) variability of sleep, and (c) interindividual (i.e., within‐group) variability of sleep. In terms of group means, only objective sleep efficiency was significantly worse with PTSD than with primary insomnia (d = 0.54). Those with PTSD differed from those with primary insomnia on measures of intraindividual as well as interindividual variability (d = 0.48–0.73). These results suggested sleep symptoms in OEF/OIF/OND veterans with PTSD are more variable across nights and less consistent across patients relative to sleep symptoms in insomnia patients without PTSD. These findings have implications for research, as well as for personalizing treatment for individuals with PTSD. Resumen Las alteraciones del sueño son prevalentes en Trastornos por Estrés Postraumático (TEPT) y están relacionados con consecuencias adversas de la salud. Hay pocos estudios que hayan utilizado métodos de valoración detallada para caracterizar el sueño en veteranos con Trastorno por Estrés Postraumático de la Operation Iraqi Freedom/Operation Enduring Freedom, Operation New Dawn (OIF/OEF/OND/). Veteranos de (OIF/OEF/OND/) con TEPT y alteraciones del sueño (n = 45) fueron comparados con pacientes con Insomnio Primario (n = 25) y sujetos controles sanos (n = 27). Los participantes fueron evaluados con cuestionarios basados tanto en mediciones diarias subjetivas y objetivas de sueño. Los 3 grupos fueron comparados en cuanto a: a) grupo promedio; b) variabilidad de sueño intraindividual (por ejemplo noche por noche) y c) variabilidad de sueño interindividual (dentro del grupo). Respecto al grupo promedio sólo la eficiencia objetiva del sueño fue significativamente peor en el grupo con TEPT que en el grupo con Insomnio Primario (d = 0,54). El grupo con TEPT discrepó tanto en la variabilidad del sueño intraindividual como en la variabilidad del sueño interindividual con el grupo con Insomnio Primario (d = 0,48 a 0,73). Estos resultados sugieren que los veteranos OEF/ OIF/OND con TEPT son más variables durante la noche y menos consistentes que los pacientes con Insomnio Primario sin TEPT. Estos hallazgos tienen implicancia tanto para la investigación como para el tratamiento personalizado en los individuos con TEPT. 抽象 Traditional and Simplified Chinese s by AsianSTSS 標題 : 軍事相關的創傷後壓力症的睡眠變異性：一個跟原發性失眠和健康對照的對比 撮要: 睡眠障礙在創傷後壓力症(PTSD)中普遍，並與多種不良健康後果相關。少有研究採用全面的評估方法去描繪患有PTSD 的OEF/OIF/OND退役軍人的睡眠。有PTSD 和睡眠障礙的OEF/OIF/OND退役軍人(n = 45)，跟原發性失眠患者(n = 25)和健康的對照實驗對象(n = 27)作對比。參加者以問卷為主的方式以及每日主觀和客觀的睡眠測量作評估。三個組別分別以此作對比：（一） 組別平均數；（二）個人每晚的睡眠變異性；（三）組別中的睡眠變異性。組別平均數方面，只有客觀睡眠效率在PTSD中比在原發性失眠中顯著地差(d = 0.54)。PTSD在個人跟組別中的變異性測量(d = 0.48 至 0.73)跟原發性失眠都不同。這些結果指出患有PTSD 的OEF/OIF/OND退役軍人的睡眠症狀，跟沒有PTSD的失眠患者的睡眠症狀相比，每晚的變異較大，患者之間亦較少一致。這些結果有助於研究和為PTSD患者提供個人化的治療。 标题 : 军事相关的创伤后压力症的睡眠变异性：一个跟原发性失眠和健康对照的对比 撮要: 睡眠障碍在创伤后压力症(PTSD)中普遍，并与多种不良健康后果相关。少有研究采用全面的评估方法去描绘患有PTSD 的OEF/OIF/OND退役军人的睡眠。有PTSD 和睡眠障碍的OEF/OIF/OND退役军人(n = 45)，跟原发性失眠患者(n = 25)和健康的对照实验对象(n = 27)作对比。参加者以问卷为主的方式以及每日主观和客观的睡眠测量作评估。三个组别分别以此作对比：（一） 组别平均数；（二）个人每晚的睡眠变异性；（三）组别中的睡眠变异性。组别平均数方面，只有客观睡眠效率在PTSD中比在原发性失眠中显著地差(d = 0.54)。PTSD在个人跟组别中的变异性测量(d = 0.48 至 0.73)跟原发性失眠都不同。这些结果指出患有PTSD 的OEF/OIF/OND退役军人的睡眠症状，跟没有PTSD的失眠患者的睡眠症状相比，每晚的变异较大，患者之间亦较少一致。这些结果有助于研究和为PTSD患者提供个人化的治疗。